Manejo comunicacional en clubes de fútbol femenino - Zambrano Béjar, Leonardo Gustavo (2023)
The present research work discusses the current state of communicative management in Ecuadorian women's football, focusing on its governing body, the FEF, particularly within the realm of the Instagram social media platform. With this in mind, the study aimed to: Assess the communicational efforts carried out by the Ecuadorian Football Federation on their Instagram accounts regarding the Women's Super League. To achieve this, a mixed-method research approach was adopted. It involved analyzing the posts made by the FEF account during the month of July, and comparing content related to both men's and women's football. Additionally, interviews were conducted with various stakeholders in women's football at the FEF level and among the participating teams in the Women's Super League. Furthermore, a focused study was undertaken involving 4 journalism professionals. Among the key findings, it was observed that only 7% of the posts made in July were dedicated solely to the Women's Super League. These posts received an average of 780 likes, a significantly lower number than those garnered by posts related to men's football across all categories. In conclusion, the research indicates that communicative efforts concerning Ecuadorian women's football are quite limited. This is evident due to the lack of exposure it receives on the official FEF page, especially when compared to the attention given to men's football.